Latest Evidence on Using Hormone Replacement Therapy in the Menopause (Journal of Bangladesh College of Physicians and Surgeons, 2018)
Hormone replacement therapy (HRT) is the most effective therapy of menopausal symptoms for perimenopausal and menopausal women. When HRT is individually tailored women gain maximum advantages and the risk are minimized. There are different types of hormones with different doses and different routes of delivery exist. . The use of HRT is an individual decision which women can only make once she has been given correct information and advice from healthcare professionals. HRT should be recommended in women with premature ovarian insufficiency with advice to continue until the average age of menopause at 51.4 years. This review item promotes confidence in prescribing HRT in most symptomatic women. Prescribing HRT in women with relative contraindication where evidence is limited. Quality of life is priority. Multidisciplinary approach may be necessary and informed written consent documented.J Bangladesh Coll Phys Surg 2018; 36(1): 26-32